2020
DOI: 10.1177/0003489420949581
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia and Dysphonia, a Pairing of Symptoms Caused by an Unusual Pair of Diseases: Castleman’s Disease and Myasthenia Gravis

Abstract: Objectives: To describe a case of coincident Castleman’s disease and myasthenia gravis that initially presented as rapidly progressive dysphagia and dysphonia and to review the unique pathophysiology of these two uncommon diagnoses. Methods: Case report and literature review. Results: Castleman’s disease, angiofollicular or giant lymph node hyperplasia, is a rare benign lymphoid proliferation. Traditionally, the disease is classified based on histologic and clinical characteristics. Fewer than 10 cases with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Between 2010 and 2020, 2 cases of Castleman disease were documented, one of which was associated with myasthenia gravis [ 7 , 8 ]. That patient underwent resection of a mediastinal tumor, which was complicated by a follicular dendritic cell sarcoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Between 2010 and 2020, 2 cases of Castleman disease were documented, one of which was associated with myasthenia gravis [ 7 , 8 ]. That patient underwent resection of a mediastinal tumor, which was complicated by a follicular dendritic cell sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with an anticholinesterase agent and corticosteroids was successful. The second report showed that the presence of Castleman disease in patients with myasthenia gravis increases the risk of developing a myasthenic crisis, which is considered a serious postoperative complication [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous report, up to 37.5% of these cases were associated with myasthenic crisis after surgical resection, an association much higher than the 5.4% incidence of myasthenic crisis following surgical resection of thymic epithelial tumors [8,9]. Table 1 includes the initial cases reported by Ishikawa et al, in addition to those reported after 2013 [3,[13][14][15][16][17][18]. One case of Castleman disease complicated by both myasthenia gravis and paraneoplastic pemphigus also included a myasthenic crisis; however, the crisis occurred during a hospitalization after a mucosal biopsy and not after the surgical resection of the mass [13].…”
mentioning
confidence: 99%